(3GdQSGdI GdbTjQjIs - (3YHO GdQMje Hf YHO GdcQje Hf ghGRf GdbTjQj, CHhfUQ , GdYGQa HGddg,J (B514 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj JaQO HLdGd edchJg hJhMO HLeGd LHQhJg s
(3BNQgG (B:s
(3ef jYX hdG jJYX hGfG CSCdc GdJhajb Edi PcQg s
(3GdfSNI HgG MhGTs
(3HChdg agQSJs
(3fSNI KGdKI s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs